Cervical cancer screening and treatment in Uganda - Nakisige, Carolyn (Gynecol Oncol Rep, 2017)
Cervical cancer is the leading cause of cancer death among women in Uganda. Given the high prevalence of genital human papillomavirus infection, the current unavailability of radiotherapy, and the absence of a national cervical cancer prevention and control program, these deaths will likely increase. Efforts to organize an effective cervical cancer screening and treatment program will require adequate financial resources, the development of infrastructure, training needed manpower, and surveillance mechanisms of the targeted women. Screening with VIA (visual inspection with acetic acid) and HPV DNA testing on self-collected samples with processing at a specific site could, for the first time, make national, large-scale population-based screening feasible in Uganda. Combining screening efforts with timely treatment of all screen positives for HPV infection can prevent progression to invasive cervical cancer. To date, this is the most effective intervention in closing the current prevention gap. Training of health professionals, ongoing construction of new radiotherapy bunkers, and opening of regional centers are all geared towards improving cervical cancer care in Uganda. The Uganda Cancer Institute Bill establishes the Institute as a semi-autonomous agency mandated to undertake and coordinate the prevention and treatment of cancer. Its implementation will be a milestone in cervical cancer prevention and control. However, execution will require political will and an increase in domestic and international investment.